2020
DOI: 10.21203/rs.3.rs-30661/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA BANCR Attenuates the Killing Capacity of Cisplatin on Gastric Cancer Cell through the ERK1/2 Pathway

Abstract: Background Chemotherapy-based comprehensive treatment is the most important therapeutic method for patients with advanced gastric cancer, but chemoresistance often causes treatment failure. Long non-coding RNA (LncRNA) BRAF-activated non-coding RNA (BANCR) has been shown to participate in many biological behaviors of multiple cancers. However, the biological roles of LncRNA BANCR in chemoresistance of gastric cancer remain unclear. Here, we aimed to evaluate the functions of LncRNA BANCR in the therapy of gas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Particularly, Miao et al found that the overexpression of lncRNA BRAF-activated non-coding RNA (BANCR) enhanced the resistance of GC cells to CDDP by activating the MAPK/ERK signaling pathway via upregulating the level of p-ERK1/2. Consistent with this, Ly3214996 (an ERK inhibitor) treatment reversed the BANCR overexpression-induced CDDP resistance of GC cells by decreasing the p-ERK1/2 level (53). In addition, lncRNAs can also regulate GC drug resistance by targeting the nuclear factor-kappaB (NF-kB) signaling pathway.…”
Section: Long Non-coding Rnas Target Signaling Pathways In Gastric Cancer Drug Resistancementioning
confidence: 56%
“…Particularly, Miao et al found that the overexpression of lncRNA BRAF-activated non-coding RNA (BANCR) enhanced the resistance of GC cells to CDDP by activating the MAPK/ERK signaling pathway via upregulating the level of p-ERK1/2. Consistent with this, Ly3214996 (an ERK inhibitor) treatment reversed the BANCR overexpression-induced CDDP resistance of GC cells by decreasing the p-ERK1/2 level (53). In addition, lncRNAs can also regulate GC drug resistance by targeting the nuclear factor-kappaB (NF-kB) signaling pathway.…”
Section: Long Non-coding Rnas Target Signaling Pathways In Gastric Cancer Drug Resistancementioning
confidence: 56%